Traditional Aucan knowledge on fish and plants eaten by fish along the Tapanahoni River, Suriname - Isabela Pombo Geertsma; van der Hoeven, Daan; van Andel, Tinde (Ethnobiology and Conservation, 2022)
Suriname’s freshwater systems are home to a large diversity of (endemic) fish species, and communities of Suriname’s interior strongly depend on this diversity for their nutrient intake. However, studies on traditional knowledge of the country’s freshwater fish and fish-plant interactions are scarce. Here, we present our findings of a pilot study in the Aucan Maroon community of Diitabiki (Tapanahoni river). We report the species of freshwater fish caught for food, their corresponding Aucan names and plants eaten by fish and/or used for fishing by the local population. We held semi-structured interviews and performed participant observation with fishers and forest guides in August and September 2021. We recorded 14 fish species, of which 12 were identified to species level, and recorded 16 Aucan fish names, of which nine were previously undocumented. Furthermore, we reported 11 plant species that were used for fishing and one fish poison (Tephrosia sinapou (Buc’hoz) A.Chev.). Suriname’s riverine ecosystems are threatened by gold mining activities that endanger the health of local communities, as well as the fish populations and riverine forests on which both people and fish depend. Local knowledge on fish, their feeding behavior and the flooded forests is essential for the conservation of this important Amazonian ecosystem, for the development of sustainable management plans and health education programs on mercury levels in consumption fish.